Aspergillus fumigatus extract modulates human eosinophils via NOD2 and oxidative stress - Hisashi Sasaki; Jun Miyata; Yusuke Kawashima; Ryo Konno; Masaki Ishikawa; Yoshinori Hasegawa; Ryuta Onozato; Yo Otsu; Emiko Matsuyama; Keeya Sunata; Katsunori Masaki; Hiroki Kabata; et al. (Allergology International)
Background: Aspergillus fumigatus is a pathogenic fungus known to be associated with severe asthma and allergic bronchopulmonary mycosis. However, the precise mechanisms underlying airway inflammation remain unclear. In this study, we investigated the direct modulation of human eosinophils by A. fumigatus and identified the specific mechanism of airway inflammation. Methods: Eosinophils isolated from healthy subjects were stimulated with extracts of A. fumigatus. Multi-omics analysis, comprising transcriptomic and proteomic analyses, was performed. The expression of specific factors was evaluated using quantitative real-time polymerase chain reaction and flow cytometry. Mechanistic analyses were performed using NOD2 inhibitor and N-acetyl-l-cysteine (NAC). Results: The A. fumigatus extract changed the expression of adhesion molecules (CD62L and CD11b) and CD69 on the surface of eosinophils, without affecting their viability, via nucleotide-binding oligomerization domain-containing protein 2 (NOD2) but not protease activity. Investigation using kinase inhibitors showed that A. fumigatus extract-induced modulation was partly mediated via p38 mitogen-activated protein kinases. Multi-omics analysis revealed that A. fumigatus-induced gene and protein expression profiles were characterized by the upregulation of oxidative stress-related molecules, including heat shock proteins (HSP90AA1, HSP90AB1, SRXN1, and HMOX1). NOD2 inhibitor and NAC differentially inhibited A. fumigatus-induced inflammatory changes. Additional multi-omics analysis identified that NOD2 signaling induced gene signatures different from those of interleukin (IL)-5 and elicited synergistic change with IL-5. Conclusions: A. fumigatus modulates human eosinophils via NOD2 and oxidative stress-mediated signaling. NOD2 signaling potentiated IL-5-induced activation, suggesting its pathogenic role in type 2 inflammation. NOD2 inhibitors and antioxidants can have therapeutic potential against A. fumigatus-related allergic disorders.